The Routledge handbook of German politics & culture - Colvin, Sarah; Taplin, Mark (Routledge handbooks, 2015)
"The Routledge Handbook of German Politics and Culture offers a wide-ranging and authoritative account of Germany in the 21st century. It gathers the expertise of internationally leading scholars of German culture, politics, and society to explore and explain - historical pathways to contemporary Germany - the current 'Berlin Republic' - society and diversity - Germany and Europe - Germany and the world. This is an essential resource for students, researchers, and all those looking to understand contemporary German politics and culture"--